Answer:
(1)0.39
(2)0.14
(3)0.21
(4)0.26
Step-by-step explanation:
John makes 35% of his free throw shots.
- The probability that John makes his shot =0.35
- The probability that John misses his shot =1-0.35=0.65
Sue makes 40% of her free throw shots.
- The probability that Sue makes her shot =0.4
- The probability that Sue misses her shot =1-0.4=0.6
(1)John and sue both miss their shots
P(John and sue both miss their shots)
=P(John miss his shot) X P(Sue misses her shot)
=0.65 X 0.6 =0.39
(2)John and Sue both make their shots
P(John and Sue both make their shots)
=P(John makes his shot) X P(Sue makes her shot)
=0.35 X 0.4=0.14
(3)John makes his shot and Sue misses hers
P(John makes his shot and Sue misses hers)
=P(John makes his shot) X P(Sue misses her shot)
=0.35 X 0.6=0.21
(4)John misses his shot and Sue makes hers
P(John misses his shot and Sue makes hers)
=P(John miss his shot) X P(Sue makes her shot)
=0.65 X 0.4 =0.26
<span>A=12h(a+b)
Solve for h.
</span>All these answers are incorrect
<span>A. h=2Aa+b
B.h=a+b2A
C.h=A2(a+b)
D.h=2(a+b)A
The answer is
h = A / 12(a+b)
![h = \frac{A}{12(a+b)}](https://tex.z-dn.net/?f=h%20%3D%20%5Cfrac%7BA%7D%7B12%28a%2Bb%29%7D)
</span>
Answer:
133
Step-by-step explanation:
Snellville
12v+14b = 796
General
14v+12b =738
We need to solve for v and b where v is how many on a van and b is how many on a bus
12v+14b = 796
14v+12b =738
Divide each equation by 2
6v+7b =398
7v+6b =369
Multiply the first equation by 7 and the second equation by -6
7(6v+7b) =7(398)
42v +49b =2786
-6(7v+6b) =369*-6
-42v -36b = -2214
Add these equations together
42v +49b =2786
-42v -36b = -2214
-------------------------------
13b = 572
Divide each side by 13
13b/13 = 572/13
b= 44
Now find v
6v+7b =398
6v +7(44)=398
6v +308 = 398
Subtract 308 from each side
6v = 90
Divide by 6
6v/6 = 90/6
v = 15
We want 2 b and 3 v
2b+3v = 2(44)+3(15) = 88+45=133
Answer:
x = 0
Step-by-step explanation:
Given
9 + 5x = 9 + 2x ( subtract 2x from both sides )
9 + 3x = 9 ( subtract 9 from both sides )
3x = 0 ⇒ x = 0
let's firstly convert the mixed fractions to improper fractions, and then subtract.
![\bf \stackrel{mixed}{10\frac{1}{3}}\implies \cfrac{10\cdot 3+1}{3}\implies \stackrel{improper}{\cfrac{31}{3}}~\hfill \stackrel{mixed}{13\frac{1}{2}}\implies \cfrac{13\cdot 2+1}{2}\implies \stackrel{improper}{\cfrac{27}{2}} \\\\[-0.35em] \rule{34em}{0.25pt}\\\\ \cfrac{27}{2}-\cfrac{31}{3}\implies \stackrel{\textit{using the LCD of 6}}{\cfrac{(3)27~~-~~(2)31}{6}}\implies \cfrac{81~~-~~62}{6}\implies \cfrac{19}{6}\implies 3\frac{1}{6}](https://tex.z-dn.net/?f=%5Cbf%20%5Cstackrel%7Bmixed%7D%7B10%5Cfrac%7B1%7D%7B3%7D%7D%5Cimplies%20%5Ccfrac%7B10%5Ccdot%203%2B1%7D%7B3%7D%5Cimplies%20%5Cstackrel%7Bimproper%7D%7B%5Ccfrac%7B31%7D%7B3%7D%7D~%5Chfill%20%5Cstackrel%7Bmixed%7D%7B13%5Cfrac%7B1%7D%7B2%7D%7D%5Cimplies%20%5Ccfrac%7B13%5Ccdot%202%2B1%7D%7B2%7D%5Cimplies%20%5Cstackrel%7Bimproper%7D%7B%5Ccfrac%7B27%7D%7B2%7D%7D%20%5C%5C%5C%5C%5B-0.35em%5D%20%5Crule%7B34em%7D%7B0.25pt%7D%5C%5C%5C%5C%20%5Ccfrac%7B27%7D%7B2%7D-%5Ccfrac%7B31%7D%7B3%7D%5Cimplies%20%5Cstackrel%7B%5Ctextit%7Busing%20the%20LCD%20of%206%7D%7D%7B%5Ccfrac%7B%283%2927~~-~~%282%2931%7D%7B6%7D%7D%5Cimplies%20%5Ccfrac%7B81~~-~~62%7D%7B6%7D%5Cimplies%20%5Ccfrac%7B19%7D%7B6%7D%5Cimplies%203%5Cfrac%7B1%7D%7B6%7D)